Foreign Body Imaging-Experience with 6 Cases of Retained Foreign Bodies in the Emergency Radiology Unit - Maralakunte, Muniraju; Debi, Uma; Singh, Lokesh; Pruthi, Himanshu; Bhatia, Vikas; Devi, Gita; MS, Sandhu (Archives of Clinical and Medical Case Reports, 2020)
Introduction: Retained foreign bodies are the external objects lying within the body, which are placed with voluntary or involuntary intentions. The involuntarily or accidentally, and complicated cases with the retained foreign body may come to the emergency services, which may require rapid and adequate imaging assessment. Materials and methods: We share our experience with six different cases with retained foreign bodies, who visited emergency radiological services with acute presentation of symptoms. The choice of radiological investigation considered based on the clinical presentation of the subjects with a retained foreign body. Conclusion: Patients with the retained foreign body may present acute symptoms to the emergency medical or surgical services, radiologists play a central role in rapid imaging evaluation. Radiological investigation plays a crucial role in identification, localization, characterization, and reporting the complication of the retained foreign bodies, and in many scenarios, radiological investigations may expose the unsuspected or concealed foreign bodies in the human body. Ultimately radiological services are useful rapid assessment tools that aid in triage and guide in the medical or surgical management of patients with a retained foreign body. <gdiv></gdiv>